Pengembangan Bahan Ajar Berbasis Media Cetak pada Materi Menulis Resensi Buku Siswa Kelas XI - Sahri Nova Yoga (Keguruan, 2021)
This study aims to develop teaching materials in the form of printed modules for writing book reviews for students in class XI SMA. This research method uses the 4D method by Thiagarajan without carrying out the fourth stage, namely the dissemination stage. The data collection technique used is documentation using a research instrument in the form of a questionnaire. Questionnaires are used to collect judgments from material experts and design experts as validators of the products that have been developed. The aspects of the assessment assessed by material experts are aspects of the curriculum, aspects of student development, aspects of readability, and aspects of truth. Then, the aspects assessed by the design expert were readability, typographical, graphic, and systematic aspects of preparation. The data obtained will be processed using Miles and Huberman data analysis techniques. Based on this development research, the resulting product is a printed module and has been validated by material experts and design experts. The average value of material experts is 3.7 with very valid criteria, and design experts with an average value of 3.9 with very valid criteria. So that the developed module is feasible to be tested at the next stage, namely dissemination by conducting small and large group tests.